Anticipating the Impact of Pornography through Dissemination of Negative Content - Hafiar, Hanny; Lukman, Syauqy; Syuderajat, Fajar; Prastowo, FX Ari Agung; Priyatna, Centurion Chandratama; Sjafirah, Nuryah Asri (FISIP Universitas Atma Jaya Yogyakarta, 2019)
Pornography through the internet has penetrated visually impaired teenagers.Socialization activities are needed to anticipate negative content. Pre-research was needed to map the problem before socialization. The study aims to examine the impact of pornography and its spread among visually impaired teenagers. The method used was a correlation with samples of teenagers at Wyata Guna, Bandung. The results show there is the impact of pornography and its spread including received, stored, accessed, and distributed through the internet. Proactive action was required from parents, and institutions to prevent a visually impaired teenager from the impact of pornography.